Diversidade filogenética e fatores estruturadores de comunidades de plantas aquáticas em lagoas temporárias - Santos, Larissa Ibiapina dos (2016)
Aquatic plants of temporary ponds represent a good model for the study of community structure and their formation process as they have selected adaptations to sazonality drafted by extreme ambiental conditions these arid and semiarid environments impose. Some of these adaptations are associated with ecological traits presented by this aquatic flora, traits as growth forms and their relationship with abiotic factors that allow us to understand the occurrence of diverse populations in the aquatic environment. Our objectives were to assess the phylogenetic structure of aquatic flora in temporary environments and observe the relationship of growth forms of aquatic flora with environmental variables of soil and water. We conducted the first objective by calculating the phylogenetic diversity index (two phylogenetic metrics- NRI and NTI) in 26 temporary ponds of the semiarid region of Brazil. We also tested the presence of phylogenetic signal to the ecological characters and verified the relationship of climate, limnological and edaphic factors with the structures found. Confirming the presence of phylogenetic signal and finding a low relationship with environmental variables (less than 25% of explanation), indicating that stochastic processes, competitive interactions and efficiency in the dispersion are the main structuring forces that generate mostly lack of phylogenetic structure and its minority overdispersed structures. For the second goal we saw how the water and soil variables influence the distribution of growth forms (have worked with the same 26 pools). Having found results that contradict previous ideas that free floating forms better respond to water and rooted emersed forms respond best to the soil, since both emerging rooted hydrophytes as the free floating hydrophytes demonstrated suffer influence of the chemical composition of the soil and the water. In these relationships the major environmental variables influencing the distribution of the growth forms were nitrate and ammonia present in the water, and redox potential and the cation exchange capacity from soil.